Knoop hardness of composites cured with halogen and led light-curing units in class I restorations - Maria Cecília C. Giorgi; Luís Alexandre Maffei Sartini Paulillo (Universidade Estadual de Campinas, 2015)
Aim: To evaluate the effect of light-curing units (LCUs) on the microhardness of class I composite restorations at different depths. Methods: Two light emitting diodes (LED) (Freelight 2, Radii) and one halogen (Optilux 501) LCUs were evaluated. Thirty class I cavities prepared in human third molars were restored with a microhybrid (Charisma) and a microfilled (Renamel) resin composite. After seven days of water storage, the teeth were decoronated and the crowns were bisected mesiodistally and tested for microhardness under a 25 g load for 20 seconds. Fifteen indentations were performed at three depths for each half-crown. Results: Charisma presented significantly higher Knoop hardness number (KHN) values than Renamel. At the superficial depth, there were no statistically significant differences (p > 0.05) when Charisma was cured with both LED curing units. However, statistically significant difference (p < 0.05) was found when Charisma was light-cured with the halogen LCU. The lowest KHN value was obtained by Renamel light-cured with both LED LCUs, regardless of the composite. Nevertheless, when the microfilled composite was light-cured with the halogen LCU, hardness was significantly higher compared to those cured with LED units at all evaluated depths. Conclusions: The effectiveness of polymerization is related not only to the light-curing source, but also to the type of composite and the curing depth.